Accommodative insufficiency as cause of asthenopia in computer-using students - Amalia, Husnun; Suardana, Gusti G.; Artini, Widya (Universa Medicina, 2010)
To date the use of computers is widely distributed throughout the world and the associated ocular complaints are found in 75-90% of the population of computer users. Symptoms frequently reported by computer users were eyestrain, tired eyes, irritation, redness, blurred vision, diplopia, burning of the eyes, and asthenopia (visual fatigue of the eyes). A cross-sectional study was conducted to determine the etiology of asthenopia in computer-using students. A questionnaire consisting of 15 items was used to assess symptoms experienced by the computer users. The ophthalmological examination comprised visual acuity, the Hirschberg test, near point accommodation, amplitude accommodation, near point convergence, the cover test, and the alternate cover test. A total of 99 computer science students, of whom 69.7% had asthenopia, participated in the study. The symptoms that were significantly associated with asthenopia were visual fatigue (p=0.031), heaviness in the eye (p=0.002), blurred vision (p=0.001), and headache at the temples or the back of the head (p=0.000). Refractive asthenopia was found in 95.7% of all asthenopia patients with accommodative insufficiency (AI), constituting the most frequent cause at 50.7%. The duration of computer use per day was not significantly associated with the prevalence of asthenopia (p=0.700). There was a high prevalence of asthenopia among computer science students, mostly caused by refractive asthenopia. Accommodation measurements should be performed more routinely and regularly, maybe as screening, especially in computer users.